APLIKASI PENGOLAHAN DATA PEMBELIAN, PENJUALAN DAN PERSEDIAAN OBAT BERDASARKAN METODE MINIMAL STOK - Kurnia, Kurnia; Jemakmun, Jemakmun (JURNAL ILMIAH MATRIK, 2012)
Pharmacies Serasi Palembang is a company engaged in the sale of drugs. In data processing sales and purchase of drugs, pharmacies are still not computerized, so that the resulting process is slow. Pharmacies Serasi Palembang also still use Microsoft Excel in preparing reports. After analyzing the existing system the authors attempt to try to help solve that problem by making an application to generate information quickly and efficiently. In preparing this report, the authors use the method of minimal stock and graphical language for software modeling using UML (Unified Modeling Language), while the tool is used starting from the analysis phase to the implementation of object diagrams (object diagrams). These applications have produced the desired output ie sales invoices, reports the drug, reports the sale and purchase and also report drug data search process easier. And the expected results of the study and the proposed application can be developed and the author can provide input that is meaningful and useful to the users. Keywords: Pharmacies, C + +, C + + Builder, Microsoft Access, Minimum Stock, UML.